METHOD AND APPARATUS FOR PERFORMING SPREAD SPECTRUM OPTICAL SPECTROSCOPY - PASANDI, Mohammad Ebrahim Mousa; ROBERTS, Kim Byron; BUSCAINO, Brandon Taylor (2024)
Aspects of the subject disclosure may include, for example, generating a first set of optical signals, demultiplexing the first set of optical signals to generate demultiplexed signals, launching the demultiplexed signals into a medium, receiving from the medium a second set of optical signals, multiplexing at least a portion of the second set of optical signals to generate one or more multiplexed signals, obtaining one or more electrical signals according to one or more measurements of one or more optical fields of the one or more multiplexed signals, and generating one or more point spread functions from the one or more electrical signals. Other embodiments are disclosed.